The use of non-medicinal plants by the community of Ayah Village in South Gombong Karst Area, Kebumen, Central Java, Indonesia - ZAHRA HANUN; DANASTRI NUR ATHAYA; AINI MAR'ATUSH SHOLEKHA; CLARA ESTELITA DAMAYANTI; IRFAN ABU NAZAR; AGUSTINA PUTRI CAHYANINGSIH; EDI JUNAEDI; INOCENCIO E. BUOT JR.; AHMAD DWI SETYAWAN (Smujo International, 2023)
Abstract. Hanun Z, Athaya DN, Sholekha AM, Damayanti CE, Nazar IA, Cahyaningsih AP, Junaedi E, Buot JR IE Setyawan AD. 2023. The use of non-medicinal plants by the community of Ayah Village in South Gombong Karst Area, Kebumen, Central Java, Indonesia. Nusantara Bioscience 15: 68-78. In the homegardens of the people of Kebumen District, Central Java Province, Indonesia, especially in the karst area of Ayah Village, usually planted various plant species with many benefits. However, the knowledge of the people of Ayah Village, Kebumen, about the various benefits of plants is only known from generation to generation, passed on orally and in daily practice habits, so a study is needed to document this information. This study aimed to determine the knowledge of local communities and various types of non-medicinal plants used to fulfill people's daily lives. Data was collected through survey techniques and open interviews with a purposive sampling method with 40 respondents. An inventory of non-medicinal plants resulted in findings of 118 plant species from 59 families. The plants used consisted of 51 species of food plants, 40 species of ornamental plants, 19 species of spices, six species of animal feed, six species of firewood, five species of building materials, and two species of hedges. Some species have more than one use. Our study showed that most of the local community uses plants as food with more diverse plant species compared to other uses.